Ranking Economics Departments Worldwide on the Basis of PhD Placement - Amir, Rabah; Knauff, Malgorzata (The Review of Economics and Statistics, 2008)
Four rankings of economics departments worldwide in terms of graduate education are constructed. The central methodological idea is that the value of a department is the sum of the values of its PhD graduates, as reflected in the values of their current employing departments. Scores are derived as solutions to linear simultaneous equations in the values. The sample includes the top 58 departments, the composition of which is determined endogenously, invoking a criterion requiring more than three placements in the sample. Illuminating the current state and trends of economics PhD education, the conclusions should be of broad interest to PhD candidates, academics, and policymakers.